ChemInform Abstract: An Efficient and Facile Synthesis of 5‐(Thiophene‐2‐carbonyl)‐6‐(trifluoromethyl)‐tetrahydro‐pyrimidin‐2 (1H)‐one and 6‐(Thiophen‐2‐yl)‐4, 5‐dihydropyrimidin‐2(1H)‐one from Same Substrates under Different Conditions. Issue 23 (May 2016) - Liang‐Ce, Rong; Zha, Yunyun; Xia, Sheng; Ji, Linlin; Zhang, Jing; Cai, Peijun
Abstract: The title compounds are prepared from benzaldehydes, trifluoro(thienyl)butanedione, and urea under different reaction conditions with high yields.